Acculturation of LANSAD students to research writingDidactic and epistemological challenges (مجلة إحالات, 2026)
This article sets out to present some sociolinguistic factors impacting the teaching-learning ofFrench in scientific fields in Morocco. Thus, we will question, upstream, by means of a field surveywhich is directed towards the students of the national school of applied sciences of kénitra and thoseregistered in Master at the faculty of sciences located in the same city, the sociocognitive parametersof the students. We will then uncover the results obtained which will give us, downstream, indicatorson the linguistic and communication skills that students must acquire in order to better understandthe teaching-learning process in question.